PENGARUH PEMBERIAN PENGUATAN VERBAL TERHADAP MOTIVASI BELAJAR SISWA KELAS V UPT SPF SD INPRES MANGGALA KOTA MAKASSAR (JS (JURNAL SEKOLAH), 2025)
Abstract: This study aims to determine the effect of providing verbal reinforcement on the learning motivation of fifth grade students at UPT SPF SD Inpres Manggala, Makassar City. This study uses a quantitative approach with an ex post facto research type. A sample of 76 students was selected through random sampling techniques. The research instrument was a questionnaire with a Likert scale. The results of the t-test showed that the significance value was 0.004